Effects of increasing extruded soy-protein concentrate on growth performance of nursery pigs - N A Lenehan; N Z Frantz; C N Groesbeck; K R Lawrence; Robert D Goodband; Michael D Tokach; Joel M DeRouchey; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
Two hundred and forty barrows and gilts (initially 13.0 lb and 18 ± 2 d of age at weaning) were blocked by initial weight and were allotted randomly to one of five dietary treatments. There were eight replications (pens) per treatment, with six pigs per pen. Pigs were fed experimental diets from d 0 to 14 after weaning that included a control diet containing 40% soybean meal and diets containing 7.1, 14.3, 21.4, or 28.6% extruded soy-protein concentrate. From d 14 to 28, all pigs were fed a similar diet to determine if any carry-over effects existed from the treatment diets. From d 0 to 14, ADG and ADFI increased (quadratic, P<0.06) as extruded soy protein concentrate increased from 7.1 to 21.4%, and then decreased similar to control values when 28.6% extruded soy-protein concentrate was fed. Feed efficiency improved (linear, P<0.01) with increasing rates of extruded soy-protein concentrate in the diet. Overall (d 0 to 28), there were no differences observed for ADG or ADFI, but F/G improved (linear, P<0.01) as extruded soy-protein concentrate increased in the diet. These results indicate that an inclusion rate up to 21.4% of extruded soy-protein concentrate was optimal for nursery-pig performance during the first two weeks postweaning.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Swine; Growth; Extruded soy protein concentrate; Pigs; Weanling pigs